The Science of Hydration: Its Impact on Endurance and Performance in Athletes - Liang Wei (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
By exploring the complex and dynamic realm of fluid dynamics within the human body, "The Science of Hydration: Its Impact on Endurance and Performance in Athletes" reveals the significant effects of hydration on athletic greatness. This investigation covers essential physiological functions, highlighting the complex function of water in preserving homeostasis. The research study used smart PLS software and generated informative results, including descriptive statistics, correlation coefficient, and that smart PLS Algorithm model between the science hydration, endurance and performance in athletes. The research explains the effects of dehydration on everything from muscle endurance to cognitive function, emphasizing the complex relationship between electrolyte balance and peak performance. The trip continues with customized hydration plans that take into account the different demands of athletes participating in different sports. Using wearables, innovations, and state-of-the-art technology, the research imagines a future in which athletics and science will come together to alter the parameters of athlete care. Beyond academic discussion, the research study is a useful road map that strongly emphasizes educating and empowering athletes to choose their hydration strategies wisely. This study captures the spirit of an all-encompassing investigation, a voyage across the rivers of scientific knowledge, technological integration, and customized methods. It invites participants and sports fans to embrace the science of hydration as a keystone to realizing human performance to the complete.